Factors Influencing Access to Health Services and Choice to Give Birth at Home: A Scoping Review - Sandra da Costa Neto; Mufdlilah; Askuri (Universitas STRADA Indonesia, 2025)
Background: The increase in the number of home births highlights the importance of understanding the factors that influence access to health services for childbirth. Purpose: The aim of this scoping review was to identify the best evidence on factors influencing access to health services and choice to give birth at home. Methods: The database was searched from 2019 to 2024 from various databases, including PubMed, Science Direct, and Wiley. As well as using search engines such as Google Scholar and Research Rabbit and selecting them using Mendeley's help. Critical appraisal and data charts were adopted from the JBI checklist, including cross-sectional, case-control, and qualitative exploratory JBI. From the 1598 articles identified, only eleven met the inclusion criteria. Results: The results of this review identified three themes, including factors influencing access to health services for home birth, the impact of limitations and the main barriers faced by mothers. Conclusion: Access to health services for mothers who give birth at home is limited by various factors, including but not limited to geography, economy, education, socio-culture, and occupation, among others. Improving access to maternal health services should focus on more affordable facilities, better maternal and family health education, and socio-cultural changes that support delivery in health facilities. As a result, these barriers reduce the utilization of health facilities, which increases the risk of complications and maternal mortality.